Pertanggungjawaban Pidana Korporasi dalam Tindakan Perpajakan: Upaya Optimalisasi Penerimaan Negara dari Sektor Pajak - Yoserwan Yoserwan (Jurnal Penelitian Hukum De Jure, 2023)
Tax crimes can be committed by taxpayers which include individuals as personal taxpayers and corporate taxpayers as taxable companies. The problem in the enforcement of tax criminal law is the unclear rules regarding corporate criminal liability in tax crimes. This article aims at discussing corporate criminal liability in tax crimes and its application in the investigation and prosecution process. The research uses normative legal research by collecting secondary data. They are primary legal sources and secondary legal sources. The results show that in handling tax crimes, both the investigators and prosecutors are doubtful to process the criminal liability of a corporation. The cause is the lack of clarity in the tax laws. As a result, criminal liability is just addressed to individual taxpayers as material perpetrators, even though the crime occurred within the scope of work of a corporation. Meanwhile, the corporation cannot be held criminally responsible. Thus, the shareholders, cannot also be held criminally responsible. Therefore, it is necessary to amend the current tax laws, so that a corporation can be prosecuted and punished for corporate crime. It is then expected that the compliance of corporations as the taxpayer will increase, and at the same time, tax evasion by corporations could be prevented. Finally, it is hoped that it will increase state revenue from the tax sector.